Codifica, inferenze ed aspetti (non?) vero-funzionali nei periodi ipotetici - Mazzoleni, Marco (Verbum – Analecta Neolatina, 2025)
In the cooperative process of meaning construction the addressee’s contribution is relevant, with an interpretative work that appears more evident when there is a gap between the “sentence meaning” and the “speaker meaning”, i.e. in the area of discourse implicits that derive from inferential processes, and which at least in some cases depend on the interaction between the linguistic forms used by the sender on the one hand and the encyclopedic knowledge and conceptual structures generally shared between the interlocutors on the other. In this contribution I intend to address with this perspective two relevant issues in the area of conditional constructions: the status of conditional perfection and that of counterfactuality, also trying to verify if and how the inferential processes involved (which in both cases deal with truth-functional aspects) can be identified with the particularized or generalized conversational implicatures of the Gricean tradition.